Enhancing Teacher Competence In Implementing The Independent Learning Curriculum: The Role Of Change Management - Zakawali Al-Fathoni, Bilal (AIM: Journal of Islamic Education Management, 2023)
The implementation of the independent learning curriculum is a fundamental endeavor undertaken by the government to enhance the quality of education and learning in schools. However, this implementation is often impeded by the inadequate grasp of various principles within the independent learning curriculum among teachers. A prevailing concern is that a significant number of teachers lack a comprehensive understanding of the independent learning curriculum, leading to the non-adherence in developing lesson plans (RPP) in accordance with the principles and guidelines set forth in the independent learning policy. To address the issue of insufficient teacher proficiency in the independent learning curriculum, the School Principal proactively initiated change management activities. The research employed descriptive and verificative methods, drawing on the action research model proposed by Kemmis & McTaggart, encompassing four stages: planning, implementation, observation, and reflection. Descriptive statistical analysis and interactive analysis techniques were employed for data analysis, utilizing various research instruments such as researchers, tests, observation sheets, and questionnaires. The study’s results indicate that the application of change management positively influences teachers’ mastery of the independent learning curriculum, particularly in their capacity to develop effective and student-oriented lesson plans (RPP), deliver instruction tailored to students’ needs, and implement self-directed learning assessments, as outlined in the independent learning curriculum. The implementation of change management measures significantly enhanced teachers’ proficiency in mastering the independent learning curriculum at SDN 131 Cijawura. This improvement is evident in various aspects of their mastery of the independent learning curriculum, which was previously developed by the researcher. Notably, the average score increased from 71.06 in the pre-action phase, with a success rate of 27.78%, to an average score of 81.06 with a success rate of 83.33% in Cycle I, and further improved to an average score of 91.28 with a success rate of 100% in Cycle II.